2010
DOI: 10.1007/s00401-010-0674-1
|View full text |Cite
|
Sign up to set email alerts
|

The neuroinflammatory hypothesis of delirium

Abstract: Delirium is a neuropsychiatric syndrome characterized by a sudden and global impairment in consciousness, attention and cognition. It is particularly frequent in elderly subjects with medical or surgical conditions and is associated with short-and long-term adverse outcomes. The pathophysiology of delirium remains poorly understood as it involves complex multi-factorial dynamic interactions between a diversity of risk factors. Several conditions associated with delirium are characterized by activation of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
241
1
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 346 publications
(262 citation statements)
references
References 144 publications
5
241
1
9
Order By: Relevance
“…Proinflammatory cytokines have been shown to lead to synaptic and neuronal dysfunction and to subsequent neurobehavioural and cognitive symptoms that are characteristic of delirium. 31 Although the incidence of embolic events was low, it is possible that emboli contributed to the postoperative delirium given that the theories regarding the pathogenesis of deliriumneuronal aging, oxidative stress, neurotransmitter and New ischemic lesion in MRI 7 (8%) ICA = internal carotid artery; M1 = M1 segment of middle cerebral artery; A1 = A1 segment of anterior cerebral artery; PVH = periventricular hyper intensities; DSWMH = deep subcortical white matter hyper intensities; T2* = T2 star weighted image MRI = magnetic resonance imaging Delirium after off-pump CABG 599 neuroendocrine dysfunction, network disconnectivity -are complementary rather than competing. 32 The presence of carotid artery stenosis[50% implies the presence of chronic cerebral hypoperfusion and systemic arteriosclerosis.…”
Section: Consent Withdrawn N=1 (New Onset Claustrophobia In Mri)mentioning
confidence: 99%
“…Proinflammatory cytokines have been shown to lead to synaptic and neuronal dysfunction and to subsequent neurobehavioural and cognitive symptoms that are characteristic of delirium. 31 Although the incidence of embolic events was low, it is possible that emboli contributed to the postoperative delirium given that the theories regarding the pathogenesis of deliriumneuronal aging, oxidative stress, neurotransmitter and New ischemic lesion in MRI 7 (8%) ICA = internal carotid artery; M1 = M1 segment of middle cerebral artery; A1 = A1 segment of anterior cerebral artery; PVH = periventricular hyper intensities; DSWMH = deep subcortical white matter hyper intensities; T2* = T2 star weighted image MRI = magnetic resonance imaging Delirium after off-pump CABG 599 neuroendocrine dysfunction, network disconnectivity -are complementary rather than competing. 32 The presence of carotid artery stenosis[50% implies the presence of chronic cerebral hypoperfusion and systemic arteriosclerosis.…”
Section: Consent Withdrawn N=1 (New Onset Claustrophobia In Mri)mentioning
confidence: 99%
“…One of the earliest changes during sepsis, due to pro-inflammatory cytokines, is microglial activation which in turn leads to neuronal loss. Oxidative stress, mitochondrial dysfunction with mitochondrial-mediated apoptosis, impaired cerebral perfusion and persistent hyperglycaemia are other important mechanisms that may induce brain dysfunction [12][13][14][15][16][17][18][19] . Neurotransmitter imbalance, especially between dopaminergic and cholinergic neurotransmission, seems to play a significant role and there are other significant neurotransmitters (beta-adrenergic substances, gamma-aminobutyric acid, serotonergic agents) whose alterations affect the development of delirium 1,11 .…”
Section: Sepsismentioning
confidence: 99%
“…Delirium indicates an acute cerebral failure. Its pathophysiology is highly complex, resulting from both inflammatory and non-inflammatory processes 1,[11][12][13][14][15][16][17][18][19] . Delirium is never caused by a single factor.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, incidence of delirium within 7 days after ICU entry was 20.6% among postpartum women. Although the mechanisms underlying delirium were unknown, the accumulating evidence indicates that brain injury (Hall et al, 2013;van Munster, Bisschop, et al, 2010;van Munster et al, 2009) and inflammation (Cerejeira et al, 2010(Cerejeira et al, , 2012Dillon et al, 2017) might be involved in this process. Consistent with this statement, we also found that serum S100B and C-reactive protein levels were obviously elevated in postpartum ICU women, especially in delirium women.…”
Section: Discussionmentioning
confidence: 99%